FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MEYLISA JANUAR ISKANDAR; ESTRALITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The purpose of this study is to find out empirical evidence of some determinants of audit report lag. Audit report lag is important issue because it can affect the timeliness of accounting information releases that used by internal and external user for their decision making. There are six factors that is total asset, industry classification, current year income (loss), audit opinion, size of Public Accountant Firm and debt proportion. The research used 128 companies listed in Indonesia Stock Exchange for period 2003 till 2009. The hypotheses proposed were tested by multiple linier regression models. The result shows that industry classification, current year income (loss), and size of Public Accountant Firms have influence to audit report lag. On the other hand, total assets, audit opinion, and debt proportion have no influence to audit report lag.